Co-expression of tissue factor, TROP2, and NECTIN4 in primary and matched metastatic cervical cancer lesions - Marit L. Ulvang; Oda Fløtre Kvile; Hege F. Berg; Kathrine Woie; Ingfrid S. Haldorsen; Alessandro D. Santin; Bjørn I. Bertelsen; Camilla Krakstad; Mari Kyllesø Halle (Translational Oncology)
Background: Early detection of cervical cancer (CC) generally leads to favorable prognosis; however, survival rates drop significantly for late-stage or recurrent disease with limited treatment options. Antibody-drug conjugates (ADCs) show promise across multiple cancers but remain sparsely explored in CC. Objective: This study evaluates ADC target expression in primary and metastatic CC to identify potential ADC responders. Study Design: Membrane expression of tissue factor, TROP2 and NECTIN4 was investigated by immunohistochemistry in 522 primary and 194 metastatic CC lesions. Expression levels were scored according to the ASCO/CAP criteria and correlated with clinicopathological features and follow-up data. Results: Tissue factor, TROP2, and NECTIN4 membranous expression were cancer-cell specific and strong (3+) in 29 %, 37 %, and 4 %, and high (≥2+) in 48 %, 68 %, and 12 % of tumors, respectively. High TF and TROP2 expression were predominantly observed in squamous cell and adenosquamous histologies (p<0.001). Overall, 80 % of primary tumors exhibited high expression of at least one of the ADC targets. High levels of tissue factor and TROP2 were detected in 45 % and 70 % of the metastatic lesions, respectively. The proportion of lesions with high NECTIN4 expression was 12 % in primary tumors and 38 % in recurrent lesions. Conclusions: The ADC targets tissue factor and TROP2 are highly expressed in primary and metastatic CC. The prevalence of high NECTIN4 expression is modest in primary tumors but increases significantly in recurrent disease. These findings support the initiation of clinical trials to evaluate safety and efficacy profiles of ADCs targeting tissue factor, TROP2 and NECTIN4 in CC.